CB-LPD, MGUS, T-LGLL, and PRCA: A rare case report of 4 concomitant hematological disorders. Issue 47 (24th November 2021) - Xu, Qinhong; Yu, Jieni; Lin, Xiaoyan; Li, Youli; Zhang, Kejie
Abstract: Rationale: Monoclonal gammopathy of undetermined significance (MGUS) is a clinically asymptomatic clonal plasma cell or lymphoplasmacytic proliferative disorder. Recently, some case reports have described the association of pure red cell aplasia (PRCA) with MGUS, even with a relatively low monoclonal immunoglobulin burden. T large granular lymphocyte leukemia (T-LGLL) is a chronic lymphoproliferative disorder characterized by clonal expansion of T large granular lymphocytes, which is rare in China. There are some reports about T-LGL leukemia in patients with B-cell lymphoma; however, it is very rare that T-LGLL coexists with MGUS and clonal B-cell lymphoproliferative disorders (CB-LPD). Patient concerns: A 77-year-old man was hospitalized because of anemia. He was diagnosed with MGUS, CB-LPD, and PRCA. During the development of the disease, a group of abnormal T lymphocytes was detected by flow cytometry of peripheral blood. Diagnosis: Combining clinical manifestations with the result of T cell receptor gene rearrangement and immunophenotype, it was consistent with the diagnosis of T large granular lymphocyte leukemia. Interventions: The patient was treat with bortezomib and dexamethasone regimen, Rituximab and sirolimus. Outcomes: The patient was transfusion independent after therapies. Lessons: We report a patient with 4 concomitant hematological disorders: T-LGLL, MGUS, CB-LPD, and PRCA, aiming to represent the clinical and flow cytometry characteristics of these concomitant diseases, analyze the mechanism between diseases, and provide a clinical reference.